2016
DOI: 10.4028/www.scientific.net/amm.821.3
|View full text |Cite
|
Sign up to set email alerts
|

Fatigue Testing of Polymeric Hollow Fibre Heat Transfer Surfaces by Pulsating Pressure Loads

Abstract: This article deals with fatigue tests of polymeric hollow fibre heat transfer surfaces. The hollow fibres have an outer diameter between 0.5-0.8 mm and wall thickness 10 % of the outer diameter. These plastic heat transfer surfaces have some limitations but also many benefits. One of the limitations is the durability of plastic under fatigue loading. The heat transfer surfaces were subjected to pulsating pressure loads under different conditions (level of pressure, ambient temperature, number of cycles). First… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3

Citation Types

0
3
0

Year Published

2018
2018
2023
2023

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 7 publications
(3 citation statements)
references
References 3 publications
0
3
0
Order By: Relevance
“…Their life expectancy is dealt with in [10]. The study proves that PHFHEs with a chaotic structure are able to withstand more than one million successful pressure cycles that simulate the operating conditions.…”
Section: Introductionmentioning
confidence: 91%
“…Their life expectancy is dealt with in [10]. The study proves that PHFHEs with a chaotic structure are able to withstand more than one million successful pressure cycles that simulate the operating conditions.…”
Section: Introductionmentioning
confidence: 91%
“…Determination of the lifetime is an important factor in every device evaluation. Fatigue testing by pressure loading proved that chaotic PHFHEs are able to withstand more than one million pressure cycles (from 0 to 3.5 bar) without any sign of damage [ 46 ]. These PHFHEs are used in this study.…”
Section: Introductionmentioning
confidence: 99%
“…They can also be used effectively in heating, ventilating and air conditioning technology. 3 The service life testing of such heat exchangers is described in the study by Brozova et al 4 More information can be found in the works of Astrouski, 5 Astrouski et al 6 and Raudensky et al 7…”
Section: Introductionmentioning
confidence: 99%